THE OPTIMIZATION OF SELECTION METHOD IN INCREASING THE EFFECTIVENESS OF WORKFORCE PLACEMENT - Sumarsid, Sumarsid (International Journal of Economy, Education and Entrepreneurship (IJE3), 2023)
Testing selection methods is a key element in effective human resource (HR) management. The aim of this research is to evaluate various selection methods with a focus on increasing the accuracy and precision of employee placement in the work environment. Through a comprehensive analysis approach to the selection strategies that have been implemented, this research identifies a number of validation techniques that have the potential to improve the selection process, thereby achieving a better match between employees and the jobs they apply for. This research uses qualitative methods by testing testing techniques through a series of case studies involving companies from various industrial sectors. The case study results show that the use of appropriate testing techniques can significantly improve the quality of the employee selection and placement process. The practical implications of this research highlight the importance of integrating robustly tested selection methods in HR management practices. This qualitative research provides an in-depth understanding of how validation techniques can be adapted to a company's specific context, thereby ensuring more efficient and productive recruitment within the organization. This research not only offers a theoretical contribution to the understanding of optimizing selection methods, but also provides practical insights for HR managers in developing more effective and efficient recruitment policies.